Induction of apoptosis through oxidative stress-related pathways in MCF-7, human breast cancer cells, by ethyl acetate extract of Dillenia suffruticosa - Tor, Yin Sim; Saiful Yazan, Latifah; Foo, Jhi Biau; Nurdin, Armania; Cheah, Yoke Kqueen; Abdullah, Rasedee; Imam, Mustapha Umar; Ismail, Norsharina; Ismail, Maznah (BioMed Central, 2014)
Background Breast cancer is one of the most dreading types of cancer among women. Herbal medicine has becoming a potential source of treatment for breast cancer. Herbal plant Dillenia suffruticosa (Griff) Martelli under the family Dilleniaceae has been traditionally used to treat cancerous growth. In this study, the anticancer effect of ethyl acetate extract of D. suffruticosa (EADs) was examined on human breast adenocarcinoma cell line MCF-7 and the molecular pathway involved was elucidated.